Identification of the population source of free-ranging cats threatening endemic species on Tokunoshima Island, Japan - Kazuaki Kazato; Yuya Watari; Tadashi Miyashita (Mammal Research, 2020)
Free-ranging cats Felis silvestris catus are harmful to endemic species, especially on islands. Effective management practices require an understanding of their habitat use and population source at the landscape level. We aimed to identify the source of the free-ranging cat population on Tokunoshima Island, Japan, which harbors a variety of endemic organisms as well as human settlements. Trapping data for the whole island were provided by local governments, and landscape factors (residential, agricultural, and woodlot areas and cattle barn density) affecting cat density were explored. An analysis of live-capture data indicated that the density (per 1 km 2 ) of free-ranging cats was positively correlated with the densities of cattle barns and woodlot areas and negatively correlated with residential areas. An interview survey revealed that nearly half of the cattle barns feed free-ranging cats. The source habitat of free-ranging cats appears to be areas with a high density of cattle barns and a high percentage of woodlots in human-dominated landscapes. Feeding cats in cattle barns may strengthen the bottom-up process of population growth on the island. To reduce the impact of cats on endemic species on Tokunoshima Island, efforts to stop feeding cats in cattle barns are important. Reaching a consensus with stakeholders will require further studies of the ecological risks posed by free-ranging cats.